PROFIL INDUSTRI KECIL MAKANAN TRADISIONAL (STUDI KASUS PADA UD.KEMAS DI KABUPATEN BENGKALIS) - Asniati "; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was conducted on UD. Kemas, Bengkalis regency. The purpose of this study is to knows industry profile of UD. Kemas as a traditional foods small industry in Bengkalis regency from financial aspects, labor aspects, production aspects, and sales aspects because UD. Kemas is a big one of small industries in Bengkalis regency which has a good quality.This research is a descriptive study with a qualitative approach. Where non population and sample. This study using key informan to obtain the information needed. The data used are primary data and secondary data. The primary data obtained from interview with owner of UD. Kemas about industry profile of UD. Kemas. Secondary data obtained from archives about how to make a dodol, lempuk durian, and dragon fruit crackers.From the analysis conducted known that; in financial aspects, profit UD. Kemas in 1 month is Rp. 2.652.250,-, or Rp. 31.827.000,-/year. Labor aspects, UD. Kemas have 18 workers. Production Aspects, the production process is carried out as many as 20 times in 1 month with output is 410 boxes dodol in 1 production. Lempuk produced 3 times in 1 year with output is 45 Kg lempuk. dragon fruit crackers produced 2 times in 1 month with output is 200 packages. Sales aspect, in 1 month UD. Kemas sell 1870 boxes dodol with price of dodol is Rp. 12,500, -/box, but dragon fruit dodol have a price is Rp. 15,000,-/box. Lempuk have a price is Rp. 100,000,-/Kg, and 15.000, - / ¼ pac for dragon fruit crackers. UD. Kemas sell all of product at stores and souvenir and tradisional foods center of Bengkalis.Keywords: Profile, Financial Aspects, Labor Aspects, Production Aspects, Sales Aspects